Baseline closure model for dispersed bubbly flow: Bubble coalescence and breakup. (27th January 2015) - Liao, Yixiang; Rzehak, Roland; Lucas, Dirk; Krepper, Eckhard
Abstract: A set of closures for two-fluid modelling of adiabatic bubbly flows has been defined as baseline model, which provides a common basis for further improvement and development. It includes closures for bubble forces, bubble-induced turbulence as well as bubble coalescence and breakup. In this work, the baseline model is implemented in the commercial code ANSYS CFX 14.5 and applied to the case of adiabatic upward vertical pipe flows. Special attention is paid to the performance of the newly proposed coalescence and breakup model. The comparison with measurements shows that the baseline model is able to capture the evolution of bubble size distribution, gas volume fraction and velocity profiles along the pipe over a wide range of flow conditions. Highlights: A baseline closure is specified for adiabatic poly-disperse bubbly flows. Coalescence and breakup model is the focus of the current work. Without any adjustment satisfying agreement is achieved for many test cases. Considerable progress in modelling of bubble coalescence and breakup is made.